The SIOP-Renal Tumour Study Group consensus statement on flank target volume delineation for highly conformal radiotherapy - Janssens, Geert O.; Melchior, Patrick; Mul, Joeri; Saunders, Daniel; Bolle, Stephanie; Cameron, Alison L; Claude, Line; Gurtner, Kristin; van de Ven, Kees P; van Grotel, Martine; Harrabi, Semi B.; Lassen-Ramshad, Yasmin; et al. (The lancet child & adolescent health, 2020)
For decades, radiotherapy with two opposing photon beams has been the standard technique used to cover the flank target volume in paediatric patients with renal tumours. Nowadays, many institutes are implementing advanced radiotherapy techniques that spare healthy tissue. To decrease the radiotherapy dose to healthy structures while preserving oncological efficacy, the conventional approach of flank irradiation has been adapted into a guideline for highly conformal flank target-volume delineation by paediatric radiation oncologists and representatives of the International Society of Paediatric Oncology's Renal Tumour Study Group (SIOP-RTSG) board during four live international consensus meetings. The consensus was refined by delineation exercises and videoconferences by ten collaborating paediatric radiation oncologists. The final guideline includes eight chronological steps to generate the tumour bed and clinical, internal, and planning target volumes, and it describes the optional use of surgical clips to optimise treatment planning. This guideline will be added into the radiotherapy guideline of the UMBRELLA SIOP-RTSG protocol for paediatric renal tumours to improve international consistency of highly conformal flank target-volume delineation.